Diagnostic Approaches and Established Treatments for Adult T Cell Leukemia Lymphoma - Tsukasaki, Kunihiro; Marçais, Ambroise; Nasr, Rihab; Kato, Koji; Fukuda, Takahiro; Hermine, Olivier; Bazarbachi, Ali (Frontiers in Microbiology, 2020)
Adult T-cell leukemia-lymphoma (ATL) is a distinct mature T-cell malignancy caused by human T-cell leukemia/-lymphotropic virus type I (HTLV-1) endemic in some areas in the world. HTLV-1 transmit through mother-to-child infection via breast feeding, sexual intercourses, and blood transfusions. Early HTLV-1 infection through presumably mother milk, is crucial in developing ATL. The estimated cumulative risk of the development of ATL in HTLV-1 carriers is a few percent after transmission from their mothers. The median age of ATL onset is about 70 in Japan and increasing now, whereas an overall mean age in the mid-forties is reported in other parts of the world. The variety in clinical features and prognosis of patients with ATL has led to its classification into acute, lymphoma, chronic, and smoldering clinical types defined by organ lesions and LDH/calcium values. In aggressive ATL (acute, lymphoma or unfavorable chronic types), and indolent ATL (favorable chronic or smoldering types), intensive chemotherapy followed by allogeneic stem cell transplantation and watchful waiting until disease progression has been recommended, respectively in Japan. Based on a worldwide meta-analysis and multiple other retrospective studies, the antiviral combination of interferon alpha (IFN) and zidovudine (AZT) is recommended in many parts of the world in acute, chronic and smoldering ATL whereas patients with the lymphoma subtype are treated with chemotherapy, either alone or combined with AZT/IFN. Several new agents have been approved for ATL by Japanese FDA after clinical trials, including an anti-CC chemokine receptor 4 monoclonal antibody, mogamulizumab, an immunomodulatory agent, lenalidomide, and anti-CD30 antibody/drug conjugate, brentuximab vedotin.